PERFORMANCE ASSESSEMENT OF ELECTRIC POWER DISTRIBUTION NETWORK BASED ON RELIABILITY INDICES - Diamenu, Godwin; Kwarteng, Joseph (International Journal of Applied Power Engineering (IJAPE))
This paper assessed the performance of a selected 33 kV electric power distribution network within the Western region of Ghana which is one of the ten geographical regions of the country. Reliability indices were computed for the performance assessment of the electric power distribution line outages. A total of 2929 outages were recorded for the selected electric power distribution line routes within the region. The historical outage data used for the performance assessment was obtained from the regional office of the Electricity Company of Ghana (ECG). The ECG regional office is in-charge of operation and maintenance of all electric power distribution networks within the Western region of Ghana. The performance assessment was carried out by computing the mean-time-to-failure (MTTF), mean-time-to-repair (MTTR) and other reliability indices.